Log-in, Track-it and Customer-Care: Women’s Perspective of Queueing Technology System in Healthcare in Kenya - Margaret Mtange (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
Customer relationship management system in healthcare is a key strategy in efficient hospital services. To enhance customer relations and service in healthcare, hospitals are adopting innovative technology to improve customer satisfaction, loyalty, and profitability by acquiring, developing and maintaining effective customer relations and interactions. There are significant researches in areas such as telecommunication, banking and manufacturing but limited in healthcare in Africa. This study is an analysis of the queuing system in an outpatient clinic in Nairobi, Kenya. This study interrogates the queueing system at the healthcare facility waiting lobby from an African’s women patients’ perspective. The study uses the contingency theory to interrogate the perspectives the element of accommodation and advocacy service quality and culture. The study utilized the exploratory research design to interrogate these perspectives. The results show that the women patients have adopted the queueing system but still require personalized (human interaction) service when calling the patient, the use of follow-up using contact details that were used during registration. This study hopes to sensitize hospital management to evaluate the impact of the queueing system on customer experience, particularly women patients.